ANALYSIS OF FINANCIAL STATEMENTS USING THE SHARIA CONFORMITY AND PROFITABILITY (SCNP) MODEL IN ASSESSING FINANCIAL PERFORMANCE OF PT. BANK MUAMALAT INDONESIA TBK PERIOD 2015-2019 - Sukmawati; Hasbi, Hasbi; Haslindah (Institut Agama Islam Negeri Lhokseumawe, 2023)
Financial statements are records of the financial information of a company for a certain period that can be used to describe the company's performance. Financial statements aim to provide financial information in a company at a certain time period that can be used by parties who need financial statements. This study aims to determine the financial performance of Bank Muamalat Indonesia for the 2015-2019 period using the Sharia Conformity and Profitability (SCnP) Model. This research is a descriptive qualitative research with documentation method. The data used is secondary data in the form of financial reports obtained from the official website of Bank Muamalat Indonesia. This study assesses two indicators, namely Sharia Conformity and Profitability, Sharia Conformity can be measured using investment, income and profit sharing ratios. While Profitability can be measured using ROA, ROE and Profit Margin. The results of the study using the Sharia Conformity and Profitability (SCnP) Model at Bank Muamalat Indonesia show the distribution into two different quadrants, namely in the Lower Right Quadrant (LRQ) and Lower Left Quadrant (LLQ). Kata kunci: laporan, keuangan, bank, kesesuaian syariah dan profitabilitas.